2012
DOI: 10.1371/journal.pone.0032103
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant and Extensively Drug-Resistant Tuberculosis in Multi-Ethnic Region, Xinjiang Uygur Autonomous Region, China

Abstract: BackgroundThe multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) has emerged as a global threat. Xinjiang is a multi-ethnic region and suffered second highest incidence of TB in China. However, epidemiological information on MDR and XDR TB is scarcely investigated.Methodology/Principal FindingsA prospective study was conducted to analyze the prevalence of MDR and XDR TB and the differences of drug resistance TB between Chinese Han and other nationalities population at Chest Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
3
24
2
2
Order By: Relevance
“…The percentage of XDR-TB was higher than in the previous surveillance data in China [16][17][18][19], in Taiwan [20], and in other countries [9,21,22], and it was similar to the 23.9% which was reported from South Africa in TB and HIV co-infected patients [23][24][25], similar to the 23.59% from nationwide population-based survey in China [5] and to 20.0% found in the study from Shandong [6]. The high prevalence of XDR-TB could be explained by the fact that our study subjects were from provincial Tuberculosis Specialized Hospitals, where the patients might tend to be selected as being relatively difficult cases.…”
Section: Discussioncontrasting
confidence: 71%
“…The percentage of XDR-TB was higher than in the previous surveillance data in China [16][17][18][19], in Taiwan [20], and in other countries [9,21,22], and it was similar to the 23.9% which was reported from South Africa in TB and HIV co-infected patients [23][24][25], similar to the 23.59% from nationwide population-based survey in China [5] and to 20.0% found in the study from Shandong [6]. The high prevalence of XDR-TB could be explained by the fact that our study subjects were from provincial Tuberculosis Specialized Hospitals, where the patients might tend to be selected as being relatively difficult cases.…”
Section: Discussioncontrasting
confidence: 71%
“…The reported percentage of XDR-TB strains among MDR-TB strains varies between provinces in China, ranging from 6.3% to 18.7% (13,15,16,(22)(23)(24). Our results showed that the proportion of XDR-TB isolates in this study was 10.2% (13/128 isolates).…”
Section: Discussionmentioning
confidence: 42%
“…The information on the prevalence of multidrug-resistant (MDR) and extensively drug-resistant (XDR TB) remains scant in the region, due to TB drug susceptibility testing (DST) not being implemented as a routine test at most hospitals. It was performed in combination with a clinical study in Urumqi from 2009 to 2011, and indicated a prevalence of MDR TB of 13.2% [13]. …”
Section: Introductionmentioning
confidence: 99%